Circular Economy: Challenges In the Reuse of Building Materials - Case Study in a Port Project at a Greek Island - Gouloumis, Spiridon; Michas, Spyros (Technical Annals, 2024)
As economies shift from a linear to a circular model — emphasizing prolonged use and reuse of resources — the reuse of building materials becomes imperative, especially in resource-constrained environments like Greek islands. This paper presents a case study involving the attempt το reuse of precast concrete blocks and embankment materials from a previously abandoned port project at Amorgos Island. The original construction was halted, leaving substantial materials deposited on a nearby beach. Nearly two decades later, a new port design incorporated most of these materials. While several technical challenges arose, all materials were eventually reused either in their original form or as fill material. The project not only reduced the environmental footprint by minimizing waste and resources extraction but also restored the affected beach area, gaining public acceptance.